2005
DOI: 10.1097/01.mib.0000161916.20007.76
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism of the NFKB1 Promoter Is Not Associated with Ulcerative Colitis in a Spanish Population

Abstract: These results suggest that the NFKB1 -94ins/delATTG gene variation, previously associated with UC susceptibility in North Americans, does not influence either susceptibility or phenotype of UC in the Spanish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
(38 reference statements)
7
24
1
1
Order By: Relevance
“…For instance, previous studies demonstrated an association of the deletion allele with ulcerative colitis (Borm et al, 2005), but others have not identified this polymorphism as a predisposing factor to this inflammatory intestinal disorder (Fyhn, 1988;Oliver et al, 2005). The discrepancy between studies could be the result of regional and ethnic differences in genotypes, and the sample size included in these studies.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, previous studies demonstrated an association of the deletion allele with ulcerative colitis (Borm et al, 2005), but others have not identified this polymorphism as a predisposing factor to this inflammatory intestinal disorder (Fyhn, 1988;Oliver et al, 2005). The discrepancy between studies could be the result of regional and ethnic differences in genotypes, and the sample size included in these studies.…”
Section: Discussionmentioning
confidence: 94%
“…12 However, the association of À94ins/del ATTG polymorphism with susceptibility to or phenotype of UC could not be replicated in German, UK and Spanish populations. [13][14][15] The discrepancies between these studies may be explained by differences in environmental factors for UC in different populations and/or differences in the haplotypic context of the À94 del ATTG variant among the studied populations.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 97%
“…Present approaches have not been able to discern whether these other genes or the class Ⅱ genes are the true risk genes in the HLA locus. [79][80][81][82] , multiple polymorphisms in the MDR1/ABCB1 gene on chromosome 7q [83][84][85][86][87][88][89][90][91][92] , and polymorphisms in the DLG5 gene on chromosome 10q [70,[93][94][95][96][97][98][99][100][101][102] . (See section C.4.1.)…”
Section: Hla Associationsmentioning
confidence: 99%